Association between daily sitting time and sarcopenia in the US population: a cross-sectional study - Alei Zhang; Yanlei Li; Jinlei Zhou; Yuan Zhang; Shanggao Xie; Haiyu Shao; Tingxiao Zhao; Tao Tang (Archives of Public Health)
Abstract Background Sarcopenia is an age-related syndrome marked by a gradual decline in skeletal muscle mass and function. While various factors influencing sarcopenia have been studied, the link between daily sedentary time and sarcopenia remains underexplored. Method This study analyzed the association between daily sitting time and sarcopenia using data from the National Health and Nutrition Examination Survey (NHANES 2011–2018). Daily sitting time was assessed through questionnaires, while sarcopenia was measured using body mass index (BMI) adjusted appendicular skeletal muscle mass (ASM). The relationship was analyzed using weighted logistic regression models and smoothing curves. Stratified analyses and interaction testing were employed to investigate population-specific characteristics of this association. Furthermore, chi-square test and grouped logistic regression were used to further analyze the impact of vigorous activity on the relationship between the two variables. Result This study included 9998 participants with complete information. The fully adjusted model showed a significant positive correlation between daily sitting time and the prevalence of sarcopenia (OR = 1.07, 95% CI: 1.03–1.10, P = 0.0026). The group with daily sitting time ≥ 9 h had a 90% higher risk of sarcopenia compared to the < 4 h group (OR = 1.90, 95% CI: 1.22–2.84, P = 0.0040). Smooth curve fitting analysis showed a linear correlation between this relationship. Stratified analysis shows that non-Hispanic white men with a lower BMI (BMI < 25) have a higher risk of sarcopenia. Compared to those who actively participate in vigorous activities, individuals who lack recreational activities have a higher prevalence and risk of sarcopenia. Conclusion Our research has found that increased sedentary time significantly increases the risk of sarcopenia, especially among non-Hispanic white men with lower BMI. Additionally, individuals who lack vigorous physical activity also have a higher prevalence and risk of sarcopenia. Therefore, reducing sedentary behavior and increasing moderate exercise may be effective prevention strategies.